The Gender Effects of Heart Rate Variability Response during Short-Term Exercise using Stair Stepper from Statistical Analysis - Nor Aziyatul Izni Mohd Rosli; Mohd Azizi Abdul Rahman; Malarvili Balakrishnan; Takashi Komeda; Saiful Amri Mazlan; Hairi Zamzuri (Institute of Advanced Engineering and Science, 2016)
This study is aimed to explore the Heart Rate Variability (HRV) response during short-term exercise by stair stepper and to compare the finding between young healthy male and female subjects. The responses were statistically analyzed by applying independent-samples t-test statistical method. The calculation of Coefficient of Variation (CoV (%)) and the slope of the linear regression is used to assess the steadiness of the HRV. Furthermore, the results also demonstrated that female subjects had greater significant p-value of RMSSD feature and significance p-value in a LF feature is greater in male. Thus, the ongoing results demonstrated that males have the sympathetic drive and females have predominant parasympathetic drive using short-term exercise by stepper. Thus, the experiment results indicate the suitability of developing rehabilitation devices in the field of Autonomic Nervous System (ANS), research, control system and rehabilitation enginering, which may help to isolate males and females.